A fast, accurate, and generalisable heuristic-based negation detection algorithm for clinical text. (March 2021) - Slater, Luke T.; Bradlow, William; Motti, Dino FA.; Hoehndorf, Robert; Ball, Simon; Gkoutos, Georgios V.
Abstract: Negation detection is an important task in biomedical text mining. Particularly in clinical settings, it is of critical importance to determine whether findings mentioned in text are present or absent. Rule-based negation detection algorithms are a common approach to the task, and more recent investigations have resulted in the development of rule-based systems utilising the rich grammatical information afforded by typed dependency graphs. However, interacting with these complex representations inevitably necessitates complex rules, which are time-consuming to develop and do not generalise well. We hypothesise that a heuristic approach to determining negation via dependency graphs could offer a powerful alternative. We describe and implement an algorithm for negation detection based on grammatical distance from a negatory construct in a typed dependency graph. To evaluate the algorithm, we develop two testing corpora comprised of sentences of clinical text extracted from the MIMIC-III database and documents related to hypertrophic cardiomyopathy patients routinely collected at University Hospitals Birmingham NHS trust. Gold-standard validation datasets were built by a combination of human annotation and examination of algorithm error. Finally, we compare the performance of our approach with four other rule-based algorithms on both gold-standard corpora. The presented algorithm exhibits the best performance by f-measure over the MIMIC-III dataset, and a similar performance to the syntactic negation detection systems over the HCM dataset. It is also the fastest of the dependency-based negation systems explored in this study. Our results show that while a single heuristic approach to dependency-based negation detection is ignorant to certain advanced cases, it nevertheless forms a powerful and stable method, requiring minimal training and adaptation between datasets. As such, it could present a drop-in replacement or augmentation for many-rule negation approaches in clinical text-mining pipelines, particularly for cases where adaptation and rule development is not required or possible. Highlights: Negation detection, the task of determining the presence or absence of findings, is important in clinical text mining. Rule-based and machine learning approaches to negation detection are common, but dataset adaptation is time-consuming. A new negation detection algorithm, using a single grammatical distance heuristic, is presented. The algorithm exhibits high performance and stability over two datasets in two different clinical settings. The algorithm may be useful where adaptation and rule development is not required or possible.